Marine ecology in a changing world - Arias, Andrés Hugo; Menendez, María Clara (CRC Press, Taylor & Francis Group, an informa business, 2014)
"With contributions from an impressive group of Argentinean and German oceanographers, this book examines classical ecological issues relating to marine ecosystems in the context of climate change. It paints a picture of marine ecology at the crossroads of global warming. The book examines the fundamentals of marine ecology: ecosystem stability, water quality, and biodiversity in the context of the changes taking place globally. It then reviews the major marine ecosystems in the same context, from the primary producers to the big marine mammals. The chapters cover primary consumers level, benthic communities, seaweeds assemblages and wetlands ecology, fisheries, and seabirds"--Provided by publisher